Business cycles synchronization and clustering in Europe (1960–2009) - Papageorgiou, Theofanis; Michaelides, Panayotis G.; Milios, John G. (Journal of economics and business, 2010)
This paper deals with business cycle synchronization and clustering in Europe. It makes an attempt to answer some fundamental economic questions regarding European countries’ business cycles in the 1960–2009 time span, by breaking the period down into three sub-periods based on major institutional changes (i.e. 1960–1991, 1992–1999, 2000–2009) and other relevant criteria. In this context, various techniques have been used, including pair-wise correlation and the so-called rolling window approach, spectral analysis and k-means clustering. Our results seem to suggest a core–periphery distinction in Europe. Also, the paper argues that European countries increased their synchronization in the time period 1992–1999, while the 2000–2009 time span is, in general, characterised by decreasing synchronization and an increase in the number of clusters. Our findings deserve careful screening and thus future research on the subject would be of great interest.